Determining Clinically Meaningful Outcomes after Isolated Acetabuloplasty in the Context of Age and Arthritic Severity: A Retrospective Review of Prospectively Collected Data - Huyke-Hernández, Fernando A.; Samagh, Sanjum P.; Hassan, Mahad M.; Tjong, Vehniah K.; Terry, Michael A. (The Journal of Hip Surgery, 2022)
Outcomes after isolated acetabuloplasty in mixed-type femoroacetabular impingement (FAI) patients can be favorable but are relatively unknown in the context of clinically important outcome variables (CIOVs) such as minimum clinically important difference and patient acceptable symptomatic state (PASS). Prognostic roles of age and osteoarthritis (OA) in hip arthroscopy are still unclear. We aimed to evaluate isolated acetabuloplasty outcomes including CIOVs while controlling for age and arthritis.This was a retrospective review of prospectively collected data. We analyzed patients with available 1-year follow-up for Patient-Reported Outcome Measurement Information System (PROMIS) scales for Physical Function (PF) and Pain Interference (PI). Patients were divided into two age groups (< 40 years old vs. ≥ 40 years old) and two Outerbridge arthritis grade groups (grade 0–I vs. grade II–IV). Demographic, radiographic, and surgical characteristics as well as revision surgeries and complications were extracted. Our outcome was the proportion of patients that achieved values over literature-reported CIOV thresholds for PROMIS-PF and PROMIS-PI.A total of 63 patients of 96 eligible (65.6%) had minimum 1-year data. Characteristics were comparable between patients aged younger than 40 and 40 and over as well as between grade 0 to I and grade II to IV patients. Overall, average PROMIS-PF and PROMIS-PI scores improved. Approximately 81.0% of patients reached values over CIOV threshold (71.4% for PROMIS-PF, 54.0% for PROMIS-PI), with 44.4% reporting these outcomes for both PROMIS-PF and PROMIS-PI. Approximately 30.2% of patients reported values over PASS threshold for both PROMIS-PF and PROMIS-PI, with 25.4% of patients achieving values above all CIOV thresholds. Only one patient required revision surgery. When evaluating the effect of age while controlling for OA severity and vice versa, there were no significant outcome differences (p > 0.615). When comparing patients reporting values above CIOV threshold versus those that did not, there were no differences in age (41.2 ± 13.0 [37.7, 44.8] vs. 45.9 ± 13.2 [38.4, 53.4], p = 0.265) or Outerbridge grade distribution (p = 0.177).This study uses CIOVs to describe clinically meaningful isolated acetabuloplasty outcomes for mixed-type FAI. Most patients over a wide spectrum of age and OA achieved favorable clinically meaningful outcomes following surgery. Isolated acetabuloplasty can alleviate symptomatology in mixed-type FAI patients on a case-by-case basis.
Keywords: isolated acetabuloplasty; hip arthroscopy; femoroacetabular impingement (FAI); Patient-Reported Outcome Measurement Information System (PROMIS)